PARALLEL COMMUNICATION INTERFACE - Ryabov, A. V.; Shakhruhanov, O. Sh.; Ivanov, V. N.; Pereversentsev, A. F. (Одеські астрономічні публікації, 2017)
Structural circuit design of an interface working in the line as long as 30 m is developed and given. In working with computerized control systems data transmission from the central computer to peripherals and vice versa is needed. We have developed a parallel communication interface which permits to transmit an eight-bit signal in TTL-levels from the unibus of the PC-type IBM AT at a distance up to 30 meters, at a velocity up to 400 kilobyte/sec.Structural scheme of the device is given in the Figure below. Similarly is arranged the information reception in PC. A computer part of the interface is executed in the form of a circuit-board inserted into a unibus of PC. A real product of this type provides stable work of the information device as distant from the control computer as 32 meters. This system is supposed to be used in the automatic observational devices of the meridian circle.